Ditongos Fonéticos: a interferência da língua falada na escrita de alunos da zona urbana e da zona rural de São José do Norte - Amaral, Veronica Santos do (2013)
The present work investigates of writing acquisition of the falling oral diphthongs [aj], [ej] and [ow] in the town of São José do Norte/RS, as well as the relationship set between the spoken language and the written language in this process. The subjects are in 1st, 2nd, 3rd and 6th grade classes from two public schools, one in the urban area of town and one in the countryside. Three instruments were elaborated for data collection, one for oral collection and two for written collection. The oral collection instrument consists of 62 pictures which were presented to each subject through a computer. Concerning the written data collection, one instrument was elaborated for the 1st, 2nd and 3rd grade students and another for the 6th grade students. For the 1st, 2nd and 3rd grades, the instrument had the image of the pictures shown to them in the computer previously, so that they would write words about these pictures. For the 6th grade students, the instrument presented statements with blanks to be properly completed. The words in the written collection were, therefore, the same in the oral data collection. Linguistic variables were investigated such as following phonological context, morphologic category and stress, as well as extralinguistic variables such as grade, sex, school zone in order to investigate their influence in the process of graphic acquisition of the respective diphthongs. The data description was carried out by using percentages referring to the production and the deletion of glides in these diphthongs. We added, in the data analysis, statistical results, through the application of the SPSS v. 17.0 program, in order to extend the research results to an ampler sample. The results confirm the proposal of Bisol (1989) about the existence of only one vowel element in the mental representation of learners, due to the significant number of reduction found in writing produced in the initial school years. The gradual appropriation of diphthongs in writing, as well as the emergence, in oral language, of the sequences [aj], [ej] and [ow] in subjects from the 3rd and 6th grades, corroborate the possibility that these diphthongs emerge in the mental representation from the contact of the subjects with the writing. They also point out to an interference of the spoken language in the written one and an influence of writing on oral language.